The Role of the Collaborative Integrated Model (MDSIC) in Agile Software Development - Case Study and Practical Advice - José Luis Cendejas Valdéz; Gustavo Abraham Vanegas Contreras; Heberto Ferreira Medina; Alfonso Hiram Ginori González (European Scientific Journal, ESJ, 2018)
This research aims to determine the importance of the generation and application of models in the software development area, performing a comparison of existing models and their applicability. One of these models is the collaborative integrated software development model (MDSIC). There are several methodologies and models that help in software development, but most of them have processes in place that make the development more complex instead of agile. The MDSIC proposes five levels of better practices that should be followed in software development projects. Also, the model supports the main areas of knowledge proposed by the Project Management Institute (PMI), thereby generating software in line with the objectives of the organizations. The MDSIC is supported by an internet platform (MDSIC v1.0), which has been developed using Java Server Pages technology and responsive web design. This platform has generated a knowledge base using social business, thus generating an information bank helpful in obtaining the experiences of specialists, proposing best practices in building agile software projects. Therefore, this article also aims to show matching indicators and results of implementating MDSIC in software projects, evaluating the needed parameters to generate good quality software, and thus align technology with the goals of the organizations.